Comparison of community-onset Staphylococcus argenteus and Staphylococcus aureus sepsis in Thailand: a prospective multicentre observational study. (May 2016) - Chantratita, N.; Wikraiphat, C.; Tandhavanant, S.; Wongsuvan, G.; Ariyaprasert, P.; Suntornsut, P.; Thaipadungpanit, J.; Teerawattanasook, N.; Jutrakul, Y.; Srisurat, N.; Chaimanee, P.; Anukunananchai, J.; et al.
Abstract: Staphylococcus argenteus is a globally distributed cause of human infection, but diagnostic laboratories misidentify this as Staphylococcus aureus . We determined whether there is clinical utility in distinguishing between the two. A prospective cohort study of community-onset invasive staphylococcal sepsis was conducted in adults at four hospitals in northeast Thailand between 2010 and 2013. Of 311 patients analysed, 58 (19%) were infected with S. argenteus and 253 (81%) with S. aureus . Most S. argenteus (54/58) were multilocus sequence type 2250. Infection with S. argenteus was more common in males, but rates of bacteraemia and drainage procedures were similar in the two groups. S. argenteus precipitated significantly less respiratory failure than S. aureus (5.2% versus 20.2%, adjusted OR 0.21, 95% CI 0.06–0.74, p 0.015), with a similar but non-significant trend for shock (6.9% versus 12.3%, adjusted OR 0.46, 95% CI 0.15–1.44, p 0.18). This did not translate into a difference in death at 28 days (6.9% versus 8.7%, adjusted OR 0.80, 95% CI 0.24–2.65, p 0.72). S. argenteus was more susceptible to antimicrobial drugs compared with S. aureus, and contained fewer toxin genes although pvl was detected in 16% (9/58). We conclude that clinical differences exist in association with sepsis due to S. argenteus versus S. aureus .